2022
DOI: 10.1590/1809-2950/21024329022022en
|View full text |Cite
|
Sign up to set email alerts
|

Physical therapy with toys and dog-assisted therapy in infants: observational study

Abstract: This study aimed to compare physical therapy with toys with dog-assisted therapy in the neuromotor development of 4-month-old infants with and without neuromotor alterations. This is a qualitative descriptive and observational study carried out with 10 infants, who were evaluated by the Alberta Infant Motor Scale, divided into Group 1 (G1) and Group 2 (G1), and subdivided into Toy Group (TG1 and TG2) and Dog Group (DG1 and DG2) for the performance of fortnightly interventions. By the Affordances in the Home En… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…AAT can elevate IgA levels, enhancing host defenses [11]. Another study [12] concluded that a therapy dog's presence promoted better results than conventional physical therapy for infants with delayed neuropsychomotor development.…”
Section: Introductionmentioning
confidence: 99%
“…AAT can elevate IgA levels, enhancing host defenses [11]. Another study [12] concluded that a therapy dog's presence promoted better results than conventional physical therapy for infants with delayed neuropsychomotor development.…”
Section: Introductionmentioning
confidence: 99%